2021
DOI: 10.3389/fpls.2021.642601
|View full text |Cite
|
Sign up to set email alerts
|

AaPKAc Regulates Differentiation of Infection Structures Induced by Physicochemical Signals From Pear Fruit Cuticular Wax, Secondary Metabolism, and Pathogenicity of Alternaria alternata

Abstract: Alternaria alternata, the casual agent of black rot of pear fruit, can sense and respond to the physicochemical cues from the host surface and form infection structures during infection. To evaluate the role of cyclic AMP-dependent protein kinase (cAMP-PKA) signaling in surface sensing of A. alternata, we isolated and functionally characterized the cyclic adenosine monophosphate-dependent protein kinase A catalytic subunit gene (AaPKAc). Gene expression results showed that AaPKAc was strongly expressed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…It was indicated that the pear mesocarp was especially susceptible to Botrytis cinerea while the pear was immature [ 12 ]. The hydrophobicity of pear fruit cuticular wax is essential in facilitating fungal invasion by regulating the growth and differentiation of A. alternata [ 13 , 14 , 15 ]. Thus, the diffusion capacity of fungicides from peel to the external part of the pear mesocarp may play an important role in their control efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that the pear mesocarp was especially susceptible to Botrytis cinerea while the pear was immature [ 12 ]. The hydrophobicity of pear fruit cuticular wax is essential in facilitating fungal invasion by regulating the growth and differentiation of A. alternata [ 13 , 14 , 15 ]. Thus, the diffusion capacity of fungicides from peel to the external part of the pear mesocarp may play an important role in their control efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…To delete the omtI gene from the genome of A. alternata FB1, a homologous recombination method was employed ( 66 ). Due to the fact that the wild-type A. alternata FB1 is sensitive to 100 µg/mL hygromycin, we could therefore operate gene knockout in the medium containing hygromycin.…”
Section: Methodsmentioning
confidence: 99%
“…A. alternata growth and conidiation were detected as previously described [ 10 ]. Precisely, the PDA medium was inoculated with 2 µL spore suspensions (1 × 10 5 spores mL −1 ) of WT A. alternata , ΔAaCaMKs and ΔAaCaMKs -C strains and incubated at 28 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the hydrophobic and pear wax substrates stimulate the differentiation of the A. alternata infection structure [ 9 ]. At the same time, AaPKAc and AaPDEL/AaPDEH in cAMP/PKA pathway [ 10 , 11 ], AaPLCs in Ca 2+ signaling pathway [ 12 ], AaHog1 in the MAPK cascades pathway [ 13 ], and transmembrane protein AaSho1 [ 14 ] are involved in the differentiation of A. alternata infection structure under hydrophobic and pear wax substrates. However, how the pathogen responds to host epidermal signals until the initiation of the infection needs to be elucidated further.…”
Section: Introductionmentioning
confidence: 99%